A Survey on Branciari Metric Spaces - Das, Abhishikta; Bag, Tarapada (Communications in Mathematics and Applications, 2023)
The motive of this review article is to collect most of the results on v-generalized metric space and its upto date various generalizations. We try to update the literature for continuous development on the results of v-generalized metric and its generalizations.